The Unindicted Co-Ejaculator and Necrophilia: Addressing Prosecutors' Logic-Defying Responses to Exculpatory DNA Results - McMurtrie, Jacqueline (2015)
This article addresses a prosecutor’s development of new and bizarre theories, particularly in cases involving confession evidence, to explain away exculpatory DNA results. In Juan Rivera’s case, the prosecutor’s theory for why sperm found inside the 11-year-old victim on the day she was murdered did not belong to Rivera was that she had sex with someone before Rivera came along and raped (but did not ejaculate) and murdered her. The unnamed-lover theory is used so often by prosecutors that it has a moniker: “the unindicted co-ejaculator.” In the case of the Dixmoor Five, teenagers convicted of the rape and murder of a 14-year-old girl were exonerated after DNA from semen found on the victim’s body was linked to a man with a lengthy record of sexual assault and armed robbery. However, the state’s attorney accepted the possibility that the convicted rapist wandered past an open field and had sex with the deceased 14-year-old victim as a means of validating the teenagers’ confessions. The article explores strategies to prevent cases like Rivera’s, that are based on a prosecutor’s logic-defying theory of guilt, from moving forward. Although prosecutors enjoy largely unfettered discretion, they must account for their actions at different stages of the criminal proceedings before bringing cases to trial. During the investigation phase, recording interrogations provides a measure of prosecutorial accountability. During the charging phase, acknowledging confirmation bias will guard against decisions to proceed in the face of contradictory exculpatory evidence. Potential judicial solutions, such as the doctrines of judicial estoppel and judicial admission and the proposed reform of criminal summary judgment, are advanced as additional means of preventing a case based upon a logicdefying theory of guilt from proceeding to trial. This article examines the question of prosecutorial accountability through the lens of Juan Rivera’s case. Rivera spent almost twenty years in prison and underwent three trials before a court vacated his conviction, holding that the prosecutor’s theory of guilt, in the face of exculpatory DNA results, was “unreasonable” and “improbable.